Dalam Bayang-Bayang Rezim Kebenaran: Analisis Foucauldian atas Wacana Revitalisasi Danau Rawa Pening - Ade Putra Suryana; Supratiwi Supratiwi (Journal of Politic and Government Studies, 2026)
The revitalization of Lake Rawa Pening as part of a priority lake rescue program not only presents technical environmental policies, but also gives rise to a contestation of discourse between the government and residents living around the lake. The purpose of this study is to analyze the formation of discourse between the government and residents in the revitalization of Lake Rawa Pening and to examine the process of discourse contestation that occurs between the two. This study uses a qualitative approach with Foucauldian discourse analysis and the New Social Movement framework. Data to support this research was obtained through in-depth interviews, documentation, and field observations. The results of this study show that the government formed a “critical” discourse on the lake through scientific legitimacy, regulation, and institutional authority to justify revitalization, including dredging, land control, and lake expansion. On the other hand, residents construct a counter-discourse using collective memory, land ownership archives, culture, and life experiences that affirm their rights to living space. The process of discourse struggle involves the reversal of meaning, mobilization of public opinion, and the transformation of resistance into an organized New Social Movement. Based on these findings, the recommendation that can be given to the government is to change its technocratic approach to more participatory policy communication by paying attention to local narratives and the collective memory of residents. For residents, it is recommended to strengthen the consolidation of collective identity as bargaining power for advocacy with the government.